Kepastian Hukum Covernote yang Diterbitkan Notaris terkait Tidak Dipenuhinya Isi Covernote dalam Mendukung Proses Pemberian Kredit oleh Perbankan - Meirissa; Yurisa Martanti; Jelly Nasseri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Discussion on the legal certainty of covernotes issued by notaries related to the non-fulfillment of the contents of the covernote in supporting the credit granting process by banks. The method used in this study is a normative juridical research type, namely library legal research or secondary data with primary, secondary and tertiary legal materials. The results of the study The legal certainty of covernotes issued by notaries related to the non-fulfillment of the contents of the covernote in supporting the bank credit granting process is only administrative and does not have the power as an authentic deed. However, legal certainty can still be realized through clarity of the limits of the notary's authority and responsibility, the application of the principle of prudence by banks, and the availability of law enforcement mechanisms through civil, administrative, and criminal channels in the event of negligence or error.